The Impact of the 'Soft Launch Relationship' Trend on Social Media on the Relationship Health of Young Couples - Fathansyah, Wafi (Acta Psychologia, 2025)
In the era of digital intimacy, the trend of "soft launching" relationships subtly posting about a romantic partner on social media without revealing their full identity has become increasingly common among young adults. This study investigates the psychological and relational impact of this phenomenon on the health of romantic relationships. Using a qualitative approach, the research explores how the soft launch behavior reflects evolving boundaries between public and private life, and how it influences trust, communication, and emotional intimacy among couples. Data were collected through in-depth interviews and social media content analysis involving individuals aged 18–30 who actively engage in soft launching. The findings reveal that while soft launching can serve as a tool for privacy protection and gradual relationship disclosure, it may also lead to confusion, insecurity, and misaligned expectations when not accompanied by clear communication. The study highlights the importance of digital literacy and emotional awareness in navigating online relationship dynamics. Implications suggest the need for relationship education that addresses the intersection of digital behavior and emotional well-being, encouraging healthy social media practices that support rather than undermine intimacy.